Analysis of the Relationship Between Fat Mass, Body Surface Area (BSA), and the Rate of Sports Injuries Among Students of the Department of Physical Education and Sports Sciences : University of Zakho / As a Model - Abdulelah Abdulsatar , Athraa (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2024)
This study aimed to investigate the relationship between body fat mass, Body Surface Area (BSA), and incidence of sports injuries among physical education students at higher education institutions in the Kurdistan Region of Iraq, with the University of Zakho as the primary research site. This investigation addressed the increasing prevalence of sports-related injuries in university physical education programs within the distinct sociocultural and academic milieu of Kurdistan. Employing a descriptive analytical methodology, anthropometric data, sports injury information, and personal details were collected from third- and fourth-year students at the University of Zakho. The study utilized validated questionnaires, standardized physical assessments, and robust statistical analyses, including correlation and regression models. The findings revealed statistically significant associations between body composition parameters and injury rates, with notable variations across diverse sports disciplines and academic progressions. These results reflect specific athletic practices and educational paradigms prevalent in higher education institutions in the Kurdistan Region. The study concluded that body fat mass, BSA, and sport-specific variables are significant predictors of injury risk among physical education students in these institutions. These findings underscore the necessity for evidence-based and culturally appropriate injury prevention strategies tailored to the unique characteristics of sports programs in universities across the Kurdistan Region of Iraq. Implementation of such strategies could potentially enhance student health outcomes and optimize performance in physical education curricula within the higher education system of the region.